2011
DOI: 10.4236/ojst.2011.13013
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric norms for a sample of Emirates adults

Abstract: Introduction: European-American norms are still used in the orthodontic treatment of Emirates patients despite the different ethnic backgrounds of the Emirates. The purpose of this study was to formulate cephalometric norms for lateral cephalometric measurements of Emirates adults and to study gender differences. Methods: Lateral cephalometric radiographs of 176 Emirates adults, 91 males and 85 females, were selected according to the following criteria; an age range between 19 to 25 years, esthetically pleasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(56 reference statements)
5
5
1
Order By: Relevance
“…Based on dental measurements, male subjects show more protrusive incisors compared to female subjects (U1-SN, L1-MP, U1-NA, U1-APog and L1-NB) but no significant difference was found. This is consistent to the study of Abu Tayem et al, where male subjects showed more protrusive incisor compared to female subjects [1]. This result consistent to the study of Gu Y et al, there is no significantly different on dental measurement on both sexes of Chinese and Caucasian [8].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Based on dental measurements, male subjects show more protrusive incisors compared to female subjects (U1-SN, L1-MP, U1-NA, U1-APog and L1-NB) but no significant difference was found. This is consistent to the study of Abu Tayem et al, where male subjects showed more protrusive incisor compared to female subjects [1]. This result consistent to the study of Gu Y et al, there is no significantly different on dental measurement on both sexes of Chinese and Caucasian [8].…”
Section: Resultssupporting
confidence: 92%
“…In measurements on Z angle, male and female reveal no significant difference. This is similar to the study of Abu Tayem et al, where Z line of female is higher than that of male, but no significant difference was found [1].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The significant difference that was found in the STP of different groups proves that Caucasian Americans norms can't be relied on in the treatment planning of orthognathic surgical cases of Saudi population. Furthermore, AlBarakati et al compared a sample of Saudi adults to Anatolian Turkish, Japanese, Holdaway reported values and a European-American Legan and Burstone's values [17,18,19,20,21]. The results found significantly different STP values of Saudi population compared to the other facial ethnics mentioned.…”
Section: Discussionmentioning
confidence: 99%